Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1073/pnas.1219601110
|View full text |Cite
|
Sign up to set email alerts
|

Temporal association of elevated cholecystokininergic tone and adolescent trauma is critical for posttraumatic stress disorder-like behavior in adult mice

Abstract: Adolescent trauma (AT) is a common risk factor for adult-onset posttraumatic stress disorder (PTSD). However, the vulnerability to AT among different individuals varies dramatically, indicating that other cofactors are important. Despite extensive studies, the identification of those cofactors has had little success. Here, we found that after subjected to traumatic stress at postnatal day 25 (P25), a stage that is comparable to the human adolescent period, inducible/ reversible forebrain-specific cholecystokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…To analyze the impact of traumatic stress on miRNA profiles in mouse PFC, we employed a well-established mouse model for PTSD that we (28, 29, 4143) and also other research groups used, at least in slightly modified ways (4446), for previous experiments. The electric footshock-elicited murine PTSD-like syndrome can be effectively counteracted by the orally administered SSRI antidepressant fluoxetine (28, 29) and, as we published recently, lasts at least until day 60 after shock application (28).…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the impact of traumatic stress on miRNA profiles in mouse PFC, we employed a well-established mouse model for PTSD that we (28, 29, 4143) and also other research groups used, at least in slightly modified ways (4446), for previous experiments. The electric footshock-elicited murine PTSD-like syndrome can be effectively counteracted by the orally administered SSRI antidepressant fluoxetine (28, 29) and, as we published recently, lasts at least until day 60 after shock application (28).…”
Section: Resultsmentioning
confidence: 99%
“…There are two CCK receptor isoforms-CCKAR and CCKBR (IUPHAR-CCK1/2) (Hill et al, 1987;Mercer and Beart, 2004). A number of studies demonstrate a role for CCK in fear and anxiety, primarily through activation of G q -coupled CCKBR (de Montigny, 1989;Bradwejn et al, 1991;Rasmussen et al, 1993;Josselyn et al, 1995;Frankland et al, 1996Frankland et al, , 1997Areda et al, 2006;Joseph et al, 2013). Interestingly, CCK and the endocannabinoids seem to engender opposite fear responses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was reported that the 5-HT 3 receptor is colocalized with cholecystokinin (CCK) immunoreactivity, and that CCK neurotransmission is highly regulated by the 5-HT 3 receptor (Paudice and Raiteri 1991;Férézou et al 2002). Moreover, it was recently shown that CCK is involved in fear extinction (Joseph et al 2013). Therefore, CCK transmission may also contribute to the 5-HT 3A receptor-mediated extinction of fear memory.…”
mentioning
confidence: 99%